Outcomes of rescue procedures in the management of locally recurrent ampullary tumors: a pancreas 2000/EPC study - Karam, Elias; Heise, Christian; Kähler, Georg; Seyfried, Steffen; Hackert, Thilo (Surgery, 2023)
Ampullary lesions are rare and can be locally treated either with endoscopic papillectomy or transduodenal surgical ampullectomy. Management of local recurrence after a first-line treatment has been poorly studied.
Gesehen am 21.11.2023